FROM MYTHS OF GODS TO SCENTS OF EMPERORS: A HISTORICAL EXPLORATION OF PERFUMERY - Anya, Petrova; Wei , Li; Ahmed , Omar (Ayden Journal of Drug and Pharmaceutical Research, 2024)
The use of cosmetics has left a distinctive mark on civilizations across the ages. Whether in the burial of the deceased, religious ceremonies, or daily life, cosmetics have played a pivotal role in preserving health and enhancing beauty. The term "cosmetics" finds its origins in the Greek word "κοσμεῖν" (pr.cosmin), signifying adornment and decoration. Throughout history, the application of cosmetics has not only reflected the evolution of societies but has also conveyed information about social hierarchies, health progress, and societal ideals of beauty.